THE EFFECT OF RARE-EARTH DOPANT TO THE ELECTRONIC, MAGNETIC, AND OPTICAL PROPERTIES OF GAN USING GGA+U APPROXIMATION - Zaharo, Aflah
Wurtzite-GaN (w-GaN) has peculiar characteristics such as high charge mobility, high electrical conductivity, and physic-chemical properties, which offer wide applications in spintronics and optoelectronics. Atomic dopants tend to elevate those properties in the w-GaN system. We investigate the electronic, magnetic, and optical properties of w-Ga1?xRExN and w-Ga1?2xRE2xN (RE = Eu, Er, and Tm) using density functional theory (DFT) and the effect of increasing dopant concentration. We also compare between GGA and GGA+U and we find the GGA+U shows closer to the experimental values with the band gaps are 3.06 eV and 3.38 eV for Er- and Tm-doped wGaN, respectively. For electronic properties, the decreasing band gap energy value exhibits a higher static dielectric constant. For magnetic properties, the 6.25% concentration of RE dopants yields an insulating electronic structure with substantial magnetic moments. Furthermore, the magnetic moment is doubled with increasing the dopant concentration. For the optical properties, the RE-doped systems show a shifting from the UV to visible region. Moreover, the absorption peaks perform a shifting to the lower energy level related to dopant concentration and atomic number for Eu, Er and Tm, respectively. These interesting properties of RE-doped GaN is potentially applied for diluting magnetic semiconductors and spintronics.